Environmental Flow Estimation Tools: IPSR Innovation Profile - Eriyagama, Nishadi; McCartney, Matthew P.; Wickramaratne, Chaturangi; Dickens, Chris; Hafeez, Mohsin (2022)
The Environmental Flow Estimation Tools are a set of user-friendly (online and offline) software tools enabling desktop estimation of quick, coarse-scale environmental flow requirements of rivers. The input data required are time series data of monthly “natural” river flows, either measured or estimated. The tools are meant to be used by water planners and managers in making initial planning-level estimates of environmental flows, which may then be followed by more comprehensive assessments using further data related to aquatic ecology, moving beyond river flow data. Five tools are currently available, two covering major rivers and the other three specifically for estimating environmental flow requirements in the Ganges Basin, Sri Lanka, and Nepal. The tools are also useful for building capacity on environmental flow estimation, including for students and practitioners seeking to gain an initial understanding of the concept of environmental flows.